Pengembangan Pondok Pesantren Melalui Program Kewirausahaan untuk Kemandirian Pesantren - Apdan Pebriana; Dudung Dudung; D Yadi Heryadi (Mikroba : Jurnal Ilmu Tanaman, Sains Dan Teknologi Pertanian, 2024)
Islamic boarding schools (pondok pesantren) play a strategic role in developing human resources that are not only religiously competent but also economically independent. In addressing the challenges of globalization, pesantren independence can be strengthened through entrepreneurship programs that provide economic benefits, empower students (santri), and contribute to the surrounding community. This study focuses on analyzing the entrepreneurship programs at Pondok Pesantren Al Kautsar 561, which include biofloc tilapia farming and melon cultivation in greenhouses, using a descriptive qualitative approach. Data collection involved focus group discussions (FGD) with foundation administrators, teachers, students, and the local community. The findings reveal that entrepreneurship programs enhance pesantren independence by generating additional income, which is utilized for scholarships and operational activities. Entrepreneurship training equips students with practical skills in agribusiness and aquaculture, such as biofloc systems and greenhouse technology. Furthermore, these programs strengthen the relationship between pesantren and the community through community-based economic collaboration, creating job opportunities and improving local economic resilience. However, challenges such as limited resources and access to technology persist. Solutions include establishing strategic partnerships with external parties and providing training in digital marketing to ensure program sustainability.